Educational robotics as part of the International Science and Education Project "Synergy" in realizing the social needs of society on the road to the Industrial Revolution "Industry 4.0" - Khomchenko, V. K.; Gebel, E. S.; Peshko, M. S. (EAI Endorsed Transactions on Energy Web, 2018)
Features common to educational robotics and to the recent concept of the fourth industrial Revolution, "Industry 4.0", have been identified, making it possible to consider educational robotics as the basic, most suitable site To prepare rising generations to succeed in the post of industrial production. An analysis of the objectives to be achieved in organizing a session with robotic devices. It was concluded that the objectives should be adjusted to the concept of "Industry 4.0" and that the methodological material and organizational work should be refined accordingly. It is reported experiences with the use of networked technologies in the example of remote robotic equipment as a way of implementing the "Industry 4.0" ideology in the international scientific education of the Synergy project.